STRATEGII DIDACTICE INTERACTIVE - REPERE METODOLOGICE DE PREDARE/ÎNVĂŢARE PRIN COOPERARE - USM ADMIN (Moldova State University, 2009)
In this article obviously there appears the contribution of the interactive didactical strategies that are leading to the learning manner's development inside pupils' or students' group. Learning methods by co-operation means the development of communication abilities of self respect, of own personality as a teaching strategy according with the actual necessities and objectives for a modern teaching manner.